Prediction Of Lung Cancer Using Machine Learning - Mrs. Mohana Priya, R. Janani, J.K.Gokul, R.Bharanidharan (International Journal of Advanced Science and Technology, 2020)
Machine learning is the application of artificial intelligence, which gives the computer the ability to learn automatically and develop learning through experience. The process of learning is through observation. The Machine makes its observation by analyzing the data’s. Data’s are collected from various sources like laboratory test, health record’s from hospitals, or making health survey, billing records, etc. It is the method of evaluating the data point or data set to predict the results. In healthcare ML is used to predict the risk factor of disease. There are discrete set of algorithms that are being used in machine learning to make prediction, or to take decision. The main focus of this project is on classification algorithm namely random forest, K nearest neighbour, support vector classifier, support vector machine.